Analyzing the Impact of Social Media on the Development of Personality Speech at Different Stages of Ontogenesis - Бутайна Абдул-Азез Аль-Нашаш; Абдель Рахман Мітіб Алтахіне (Preschool Education: Global Trends, 2025)
Aim. This study explores the impact of social media on modern language, focusing on vocabulary, grammar, language complexity, and communication patterns. Language complexity is understood as a multifaceted concept that includes syntax, semantics, pragmatics, phonetics, phonology, and morphology. As language continually evolves alongside cultural and technological shifts, social media platforms such as Twitter, Instagram, Facebook, and TikTok have become influential spaces where language adapts and changes. This research examines how digital communication promotes the use of slang, abbreviations, emojis, and informal expressions, reshaping how users interact and express ideas online. Employing a mixed-methods approach, combining qualitative and quantitative analyses, the study analyzes language use on these platforms and identifies significant trends.